2015
DOI: 10.1590/0104-1428.1974
|View full text |Cite
|
Sign up to set email alerts
|

High shear dispersion of tracers in polyolefins for improving their detection

Abstract: SbstractAn efficient recycling of end-of-life products is of crucial interest from an economical and ecological point of view. However, the near infrared spectroscopy often used for the optic sorting processes is limited because of the absorption of carbon black present in black plastics and as it only sorts as a function of chemical formulas. The tracing technology developed in this study is based on the dispersion of lanthanide complexes particles into polymers to give them a code that can be related to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Despite the regular use of polymer extrusion to incorporate photoluminescent markers into commodity plastics, almost all reports in the literature neglect to report how the markers are dispersed in the extrusion product. An exception to this is the publication by Massardier et al, where UV photoluminescent inorganic compounds are extruded into PP under different screw rotation speeds . A 0.1 wt % loading of marker was added to PP with extrusion rotation speeds varied from 100 to 1200 rpm.…”
Section: Methods Of Incorporating Photoluminescent Labelsmentioning
confidence: 99%
“…Despite the regular use of polymer extrusion to incorporate photoluminescent markers into commodity plastics, almost all reports in the literature neglect to report how the markers are dispersed in the extrusion product. An exception to this is the publication by Massardier et al, where UV photoluminescent inorganic compounds are extruded into PP under different screw rotation speeds . A 0.1 wt % loading of marker was added to PP with extrusion rotation speeds varied from 100 to 1200 rpm.…”
Section: Methods Of Incorporating Photoluminescent Labelsmentioning
confidence: 99%
“…Therefore, in the present article, we are interested in the photodegradation of polypropylene filled with lanthanide complexes that can be used as tracers for the identification of polymer materials (especially black ones), in order to facilitate high speed automatic sorting of plastic wastes for an economically efficient recycling. The feasibility of the detection of these lanthanide complexes dispersed in white and black PP matrices was successfully achieved in previous studies [28] through the use of UV-ray fluorescence spectrometry. Furthermore, the elaboration of traced blends via high shear process [29,30] has proved to be a major key for preparation of well dispersed tracer particles within polypropylene matrix especially when processing at a screw speed, N, equal to 800 rpm.…”
Section: Introductionmentioning
confidence: 93%
“…They can even be applied as a thin fluorescent coating onto the finished plastic products or intermediates. 26,27 For instance, Massardier et al reported the incorporation of 0.1 wt % of lanthanide complex particles into a polypropylene (PP) matrix under a high shear rate (N = 800 rpm) to prepare a fluorescent polypropylene that is detectable with UV-ray fluorescence spectrometry within 10 ms. 23 Langhals et al reported using organic dyes, that is, perylene ester, perylene carboxylic bisimide, and terylene carboxylic bisimide FMs, to identify polymers by measuring the time constant of autofluorescence decay values. 25 They also demonstrated that the polymer type (styrene−polyacrylonitrile copolymer, polyoxymethylene, or polyamide) alters the fluorescence lifetime values of the incorporated markers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The use of FMs, as an accurate and cost-effective approach to identify and sort specific polymers from plastic waste streams, has received considerable attention in recent years. FMs can be incorporated in polymer matrices via masterbatches, e.g., by extrusion or injection molding. They can even be applied as a thin fluorescent coating onto the finished plastic products or intermediates. , For instance, Massardier et al reported the incorporation of 0.1 wt % of lanthanide complex particles into a polypropylene (PP) matrix under a high shear rate ( N = 800 rpm) to prepare a fluorescent polypropylene that is detectable with UV-ray fluorescence spectrometry within 10 ms . Langhals et al reported using organic dyes, that is, perylene ester, perylene carboxylic bisimide, and terylene carboxylic bisimide FMs, to identify polymers by measuring the time constant of autofluorescence decay values .…”
Section: Introductionmentioning
confidence: 99%